LESSONS LEARNED AND NEXT STEPS FOR BUILDING KNOWLEDGE ABOUT TRIBAL MATERNAL, INFANT, AND EARLY CHILDHOOD HOME VISITING. Issue 3 (16th May 2018) - Whitmore, Corrie B.; Sarche, Michelle; Ferron, Cathy; Moritsugu, John; Sanchez, Jenae G.
ABSTRACT: Authors in this Special Issue of the Infant Mental Health Journal shared the work of the first three cohorts of Tribal Maternal, Infant, and Early Childhood Home Visiting (MIECHV) grantees funded by the Administration for Children and Families. Since 2010, Tribal MIECHV grantees have served families and children prenatally to kindergarten entry in American Indian and Alaska Native (AI/AN) communities across the lower 48 United States and Alaska. Articles highlighted challenges and opportunities that arose as grantees adapted, enhanced, implemented, and evaluated their home‐visiting models. This article summarizes nine lessons learned across the articles in this Special Issue. Lessons learned address the importance of strengths‐based approaches, relationship‐building, tribal community stakeholder involvement, capacity‐building, alignment of resources and expectations, tribal values, adaptation to increase cultural and contextual attunement, indigenous ways of knowing, community voice, and sustainability. Next steps in Tribal MIECHV are discussed in light of these lessons learned.